Role of Nidana Parivarjana as a Line of Management in Pureeshaja Krimiroga (International Journal of Ayurveda and Pharma Research, 2023)
Krimi is used to denote tiny organism which reside in human body. The concept of Krimi and their relation in development of disease is mentioned by Ayurveda literature. Krimi Roga, a serious morbidity, contributes significantly to disease burden in children and causes malnourishment and stunted growth in them. Aharaja and Viharaja Nidana plays an important role in growth of Krimi. Treatment modalities mentioned for Krimiroga are Apakarshana, Prakriti Vighata and Nidana Parivarjana. Concept of Nidana Parivarjana holds important role in prevention as well as treatment of disease especially in Krimiroga.